Comparing difference in mean total protein, albumin and globulin based on severity of rhesus isoimmunization: a prospective study - Yadav, Vikas; Deka, Dipika; Sharma, Aparna; Dadhwal, Vatsla (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Maternal RBC alloimmunization results from exposure and response to a foreign RBC antigen. Transplacental fetal to maternal hemorrhage is the most common cause of alloimmunization. Rh incompatibility can lead to either fetuses with hydropic features or non-hydropic. The precise mechanism leading to the development of hydrops is uncertain. Biochemical markers have the potential to be used to assess the severity of problem. But of the mechanisms proposed none have been able to totally explain the phenomenon or predict the prognosis. Objective of this study wads to compare the difference in mean total protein, albumin and globulin bases on severity of isoimmunization and comparing it with normal controls. Methods: A Total of 40 pregnant patients were enrolled which included 10 hydropic fetuses of Rh isoimmunised mothers, 10 non hydropic fetuses of Rh isoimmunized mothers. Control group included 18 Rh positive women without any fetal complication and 2 fetuses in women undergoing cordocentesis. Blood sampling was done at time of intrauterine transfusion and sent for estimation of total proteins, albumin, globulin in fetal blood. Pregnancies were followed up till delivery and fetal outcome noted. Results: Mean total protein, albumin and globulin between hydropic, non hydropic group and control group (3.25, 2.17 and 1.18 g/dl) in hydropic, (4.14, 2.70 and 1.44 g/dl) in non hydropic and (4.42, 2.95 and 1.47 g/dl) in control group respectively. Mean total protein, albumin and globulin between mild hydropic (3.43, 2.30 and 2.10 g/dl) and severe hydropic group (2.59, 1.6 and 1.3 g/dl) respectively. Conclusions: There was significantly lower levels of serum total proteins, albumin and globulin in hydropic fetuses as compared to non hydropic fetuses. Thus, hypoproteinemia can be considered a strong marker for development of hydrops in Rh isoimmunized fetuses.